From ‘Prisons to Correctional Services’: Exploring Evidence Based Analysis of The Plight of Awaiting Trial Inmates in Kwara State, Nigeria - Ibrahim ogirima Salawu; Abubakar Yushau Yushau Alfakoro (Journal of Governance, 2024)
Inmates awaiting trial are individuals yet to be legally convicted of any crime but kept in police or correctional custody for ease of interrogation, among other reasons. This study, however, assessed the phenomenon of an increase awaiting trial inmates across correctional facilities in Nigeria, using Kwara State, Nigeria, as the study area. The study employed a survey research design with mixed data methods as methodology, in which primary data were sourced through semi-structured interviews and internet, journal, and website data as secondary data. Structural functionalism was the theoretical framework for the study. The population for the study consists of inmates awaiting trial, officials of the correctional service, police officers, and lawyers. The study revealed that an increase awaiting trial inmates has led to prison breaks, prison congestion, and an overstretch of physical infrastructure available for convicted inmates, among other challenges. The study recommended that ease and speedy judicial processes should be adhered to too; the building of special apartments for the housing of awaiting inmates’s trials should be encouraged; and budgetary allocation should be increased to components of the criminal justice system, among other recommendations.